Transcatheter mitral valve‐in‐valve and valve‐in‐ring replacement: Lessons learned from bioprosthetic surgical valve failures. Issue 11 (8th August 2021) - Aalaei‐Andabili, Seyed H.; Bavry, Anthony A.; Petersen, John; Massoomi, Michael; Arnaoutakis, George J.; Choi, Calvin; Anderson, R. David; Falasa, Matt; Beaver, Thomas M.
Abstract: Introduction: Limited data are available about the outcomes of transcatheter mitral valve replacement (TMVR) using transseptal approach in patients with prior mitral valve repair (valve‐in‐ring) or replacement (valve‐in‐valve) (TMViVR) and on modes of the prior surgical valve failures. We report our tertiary center TMVR experience in high surgical risk patients with prior mitral valve repair or replacement. Methods: From December 2016 to January 2020, patients with symptomatic severe mitral valve stenosis and/or insufficiency at increased redo surgical risk were included. TMViVR was performed off‐label with Sapien S3 valve (Edwards Lifesciences). Patients were followed within 30‐days and 1‐year from the procedure. Results: Twenty‐seven patients underwent transcatheter mitral valve‐in‐valve ( n  = 21) or valve‐in‐ring ( n  = 6) replacement. Mean ±  SD age was 71.8 ± 11 years with Society of Thoracic Surgeons' calculated mortality 7.1 ± 4.6%. The etiology of valve failure was stenosis in 17 (63%) patients, insufficiency in 4 (14.8%) patients, and both in 6 (22.2%) patients. TMViVR technical success was 100% in all patients. Left ventricular outflow track (LVOT) obstruction was observed in only one (3.7%) patient. Zero patients had moderate or severe central mitral valve regurgitation or paravalvular leak. All patients had symptomatic improvement at 30 days. The mean transmitral diastolic pressure gradient decreased from 14.1 ± 4.6 to 6.9 ± 4.6 mm Hg ( p  < .001) at 30 days. The one patient with LOVT obstruction required readmission at 5‐months. One‐year survival was 95%. At 1‐year mean gradients remained lower than the baseline (7.0 ± 3.0 vs. 12.4 ± 4.0, p  = .002). Conclusions: Transcatheter mitral valve‐in‐valve and valve‐in‐ring replacement is feasible and safe. The improvement in mitral valve hemodynamics appears to be durable.